Transforming Indonesian Language Assessment in Secondary Schools through the Rasch Model: A Conceptual Framework for Evidence-Based Assessment) - Fahmi, Royan Nur; Amanat, Tri; Zaman, Saefu (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to develop a conceptual framework for transforming Indonesian language assessment in secondary schools through the Rasch Model approach to promote evidence-based assessment. The main issue in current Indonesian language assessment lies in the dominance of classical approaches, which may lead to less objective measurement, limited accuracy in identifying students’ abilities, and insufficient support for data-driven decision-making. This study employs a conceptual research method by reviewing relevant literature on modern measurement theory and the application of the Rasch Model in education. The findings indicate that the Rasch Model offers significant advantages in producing objective measurement, enhancing the validity and reliability of assessment instruments, and enabling more in-depth analysis of item characteristics and student abilities. The proposed conceptual framework emphasizes the integration of the Rasch Model in the development, analysis, and interpretation of Indonesian language assessment instruments. The implications of this study are expected to provide a foundation for developing more accurate, fair, and evidence-based assessment systems in secondary education.